Esri Malaysia Sdn Bhd. / Hanis Haziera Hashim - Hashim, Hanis Haziera (2022)
Esri Malaysia Sdn Bhd is Malaysia's sole distributor of Esri GIS software products and services more than one thousand of the country’s leading government agencies and commercial enterprises. In this case study, it is focus on the ArcGIS desktop software which is the foundational piece of the ArcGIS platform for GIS professionals. The product was identified, investigated and analysed along to find the problems and come out with suitable solution for the product innovation. The first problem is the unfriendly and complicated interface likes toolbar interface will really takes time to learn and be familiar for the inexperienced users. It was many processing tools in GIS software and the users need to dig up to reach the desired tools. So, the simpler interface with systematic tools arrangement needs to be consider by a GIS software developer. The second problem is software crash which is suddenly not responding and stop working. Generally, the software crash is depending on the computer capabilities and the system. Thus, the developer should take an account the mitigating measure for the problem that will be occur. Esri Malaysia need to develop a tool to automatically check and monitor the system which is critical tool to prevent software crashes and mistakes. All of these problems and solutions were considered to help Esri Malaysia in developing high quality product in order to maintain their good reputation. May GIS desktop software was proposed as a new product with an additional system and function that suitable for GIS desktop software. The proposed GIS software will be design by using ribbon and equipped with the auto save, auto recovery and data backup system just like how Microsoft and AutoCAD did to their software. This product is an easy understand software with the data loss prevention. So, the users do not need to be worry about working with GIS application and their works anymore with May GIS software because it provides a platform to getting up and running with GIS technology.